PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN REKRUTMEN TERHADAP KINERJA KARYAWAN PADA PT. JAPFA COMFEED MEDAN - Adam Firmansyah; Rita Hutapea; Theodoro Hia; Natalia Stefani Sigalingging; Maduma Sari Sagala (JURNAL WIDYA, 2025)
This research is based on employee performance which plays an important role as a factor influencing the level of success and the main driver of PT. Japfa Comfeed Medan. This study aims to determine the effect of the Management Control System and Recruitment on employee performance at PT. Japfa Comfeed Medan. The research method used is quantitative descriptive with a sample of 75 respondents. Data analysis techniques include the determination coefficient test, T test (Partial), and F test (simultaneous). The results of the determination coefficient show that the determination coefficient (R Square) is 0.062 equal to 6.2%. The F test value is 2.009 and the significance value is 0.143>0.05. The t test value is - 0.32> from the t table value of 1.666 and Sig. 0.974>0.05. Thus, it can be concluded that SPM (X1) and Recruitment (X2) partially do not have a significant effect on Employee Performance (Y), because the significance value of each variable, namely 0.974 and 0.056>0.05. This shows that the implementation of SPM and recruitment in this study has not been the main driving factor in improving employee performance. Keywords: Management Control System, Recruitment, Employee Performance, PT. Japfa Comfeed Medan